Psikoedukasi mengenai Forgiveness bagi Jemaat GPdI Griya Parahita Kadusirung - Tumanggor, Raja Oloan (Journal Of Human And Education (JAHE), 2024)
Living in a pluralistic society consisting of various ethnicities, cultures and religions, such as the residential area in Kadusirung Village, Pagedangan District, Tangerang Regency, Banten, is not easy, because there is the potential for various problems to arise in society, for example misunderstandings or internal conflicts between fellow citizens. In situations like that, a positive attitude is needed, such as forgiveness, so that there is a feeling of calm and peace in humans when faced with various problems in life. Forgiveness is not only a psychological issue, but is also a priority in Christian theological views. Therefore, this PKM was carried out for 30 residents of the Pentecostal Church in Indonesia (GPdI) at the Griya Parahita housing complex in Kadusirung village. Through this PKM, congregation members are invited to understand the meaning of forgiveness from a psychological and theological perspective, with the hope that congregation members will be better able to practice forgiveness in their daily lives. Forgiveness given to people who are guilty, apart from making people feel relieved and mentally healthy, is also a manifestation of Christian faith because in the Christian theological view, every Christian must always forgive others as Christ also forgave all human mistakes. This PKM made a deep impression on the participants and they wanted similar activities to be carried out in the future.